2022
DOI: 10.1021/acssuschemeng.2c01363
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Lewis Acid Properties of Metal–Organic Framework Nodes via Anion Post-Replacement for Gas Adsorption and Separation

Abstract: Metal–organic frameworks (MOFs) with open metal sites (OMSs) have many applications from sensing, catalysis, to gas adsorption and separation. The OMSs have Lewis acid nature, which are capable of accepting electron density from guest molecules, thus enabling selective gas adsorption. The Lewis acid strength of OMSs plays a pivotal role in the adsorption properties of MOFs. In this work, we report a general method capable of adjusting the Lewis acid strength of OMSs in a cationic framework MIL-101. Relying on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…22a). 246 Operando IR spectroscopic analysis using CO as a probe revealed that the Lewis acidity of MIL-101-X samples was in the sequence MIL-101-Cl > MIL-101-F > MIL-101-COOH > MIL-101-NO 3 , which is the same as the order of N 2 O adsorption capacity (Fig. 22c).…”
Section: Separation Of N2o Using Apmsmentioning
confidence: 74%
“…22a). 246 Operando IR spectroscopic analysis using CO as a probe revealed that the Lewis acidity of MIL-101-X samples was in the sequence MIL-101-Cl > MIL-101-F > MIL-101-COOH > MIL-101-NO 3 , which is the same as the order of N 2 O adsorption capacity (Fig. 22c).…”
Section: Separation Of N2o Using Apmsmentioning
confidence: 74%
“…From Figure b, we can find that the peak intensities of free carboxylic acids at the positions of 1666 cm –1 (stretching vibration of CO in the carboxyl group –COOH) and 1444 cm –1 (deformation vibration of –OH in –COOH) disappear after NH 4 F soaking, indicating that the uncoordinated carboxylic acids in M101/P-M101 pores have been washed away by NH 4 F. The two strong bands of the samples at 1620 and 1404 cm –1 can be attributed to typical νas (–COO −) and νs (–COO – ) of carboxylate, respectively. The positions of 662 and 584 cm –1 belong to the O–Cr–O absorption peaks of BDC connected with Cr. , It is worth noting that one of the two vibrational strengths of O–Cr–O was weakened after NH 4 F modification. This result suggests that coordination around the Cr(III) centers may change.…”
Section: Resultsmentioning
confidence: 99%
“…The positions of 662 and 584 cm –1 belong to the O–Cr–O absorption peaks of BDC connected with Cr. 31 , 32 It is worth noting that one of the two vibrational strengths of O–Cr–O was weakened after NH 4 F modification. This result suggests that coordination around the Cr(III) centers may change.…”
Section: Resultsmentioning
confidence: 99%
“…Taking P / P 0 = 0.5 as the dividing point, when P / P 0 < 0.5, the adsorption of gas in the coal depends on the van der Waals force, and the adsorption amount has a strong correlation with the surface roughness of the coal, so the fractal dimension D 1 can be used to reflect the pore surface roughness. When P / P 0 > 0.5, the gas adsorption is mainly controlled by multilayer adsorption and depends on the volume structure of the pores. The more complex the pore volume structure is, the stronger the adsorption capacity is, so the fractal dimension D 2 can reflect the complexity of the pore volume structure. The fractal dimensions D 1 and D 2 should be between 2 and 3. The closer D 1 and D 2 are to 3, the greater the pore surface roughness and pore volume structure complexity are.…”
Section: Effect Of Changes In the Pore Structure Of Coal Particles On...mentioning
confidence: 99%
“…When P / P 0 > 0.5, the gas adsorption is mainly controlled by multilayer adsorption and depends on the volume structure of the pores. 39 43 The more complex the pore volume structure is, the stronger the adsorption capacity is, so the fractal dimension D 2 can reflect the complexity of the pore volume structure. 44 47 The fractal dimensions D 1 and D 2 should be between 2 and 3.…”
Section: Effect Of Changes In the Pore Structure Of Coal Particles On...mentioning
confidence: 99%